Formación médica de pregrado basada en la motivación: la realización de la docencia (2013)
Undergraduate medical formation is a complete, diverse and exciting pedagogic model that allows teaching exercise to apply all the tools, knowledge and experience in order to get an adequate learning teaching process. Because its similarities and characteristics, three stages in medical formation can be defined. The first, is training in the classroom and the laboratory for learning the basic sciences, Second, the clinic sciences study thorough clinical clerkships and third the senior student year. This last stage is the transition of the student to the professional medical practice, increasing the student autonomy and responsibility. When a medical educator is able to use all its experience applying different educational tools based on the motivation, the students achieve to consolidate their learning process towards excellence and the teacher comes to the realization in his professional practice.